The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/min13060780
|View full text |Cite
|
Sign up to set email alerts
|

Metallogenesis and Formation of the Maliping Pb-Zn Deposit in Northeastern Yunnan: Constraints from H-O Isotopes, Fluid Inclusions, and Trace Elements

Abstract: The Maliping large-scale Pb-Zn deposit is located in the Sichuan-Yunnan-Guizhou Pb-Zn polymetallic metallogenic triangle area (SYGT), where the Pb-Zn ore body is hosted in the interlayer fracture zone at the interface between siliceous cataclastic dolomite and clastic rocks in the Lower Cambrian Yuhuchun Formation and is tectonically driven. Unlike other Pb-Zn de-posits hosted in the Sinian and Carboniferous carbonate rocks in the area, the metallogenic mechanism and deep and peripheral ore prospecting predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The fluid inclusion and H-O-He-Ar isotopic data suggests that ore-forming fluids in the Maoping deposit are the result of mixing of metamorphic fluids from the Precambrian basement and basinal brines from the Youjiang Basin [6]. Similarly, the new data from the Maliping deposit suggest that the ore-forming fluids are derived from the mixing of deep sourced fluids flowing through the basement and organic-bearing basinal brines [7].…”
mentioning
confidence: 90%
“…The fluid inclusion and H-O-He-Ar isotopic data suggests that ore-forming fluids in the Maoping deposit are the result of mixing of metamorphic fluids from the Precambrian basement and basinal brines from the Youjiang Basin [6]. Similarly, the new data from the Maliping deposit suggest that the ore-forming fluids are derived from the mixing of deep sourced fluids flowing through the basement and organic-bearing basinal brines [7].…”
mentioning
confidence: 90%
“…Studies on fluid inclusions in sphalerite and gangue minerals of several major deposits in the SYGT have shown that the homogenization temperature of the inclusions ranges from 115 to 280 • C, with an average range of 150-250 • C [17,18]. The average homogenization temperature of fluid inclusions from the Maliping deposit is 255 • C [19]. At this temperature, TSR may be the main mechanism responsible for the transformation of SO 4 2− into H 2 S in the hydrothermal solution.…”
Section: S Sourcementioning
confidence: 99%